2014
DOI: 10.1111/ped.12218
|View full text |Cite
|
Sign up to set email alerts
|

Culture‐proven neonatal sepsis in preterm infants in a neonatal intensive care unit over a 7 year period: Coagulase‐negative Staphylococcus as the predominant pathogen

Abstract: Background: The aim of this study was to determine the causative agents in early, late-and very late-onset sepsis in preterm infants. The demographic features, risk factors, clinical and laboratory findings in sepsis types were also defined. Methods: A total of 151 preterm infants with culture-proven neonatal sepsis were enrolled in this prospective study. The infants were classified into three groups with regard to the onset of sepsis: early onset sepsis (EOS), late-onset sepsis (LOS) and very late-onset seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
40
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 34 publications
13
40
2
1
Order By: Relevance
“…The resistance rate of gentamicin was high in the period of 2000–2004 and then decreased. In contrast to our findings, other studies showed high levels of antimicrobial resistance to gentamicin . Since 2000, aminoglycosides have rarely been used in children in China due to ototoxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…The resistance rate of gentamicin was high in the period of 2000–2004 and then decreased. In contrast to our findings, other studies showed high levels of antimicrobial resistance to gentamicin . Since 2000, aminoglycosides have rarely been used in children in China due to ototoxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, newborns most probably acquire these Gram-negative rods from the vaginal and fecal flora of the mother and the environment during delivery. On the other hand, other investigators found that CoNS was the most common causative organism of NS [20]. However, the mortality rate due to CoNS was lower than that due to Gramnegative bacilli.…”
Section: Discussionmentioning
confidence: 89%
“…Again, these are known risk factors for the development of sepsis in this population. [12][13][14] In all cases a p value of 5% or less was set as the definition of statistical significance.…”
Section: Methodsmentioning
confidence: 99%